CREATION OF SCIENTIFIC JOURNAL REPOSITORY BASED ON OPEN JOURNAL SYSTEMS - Іванкевич, О.В.; Вахнован, В.Ю. (Proceedings of National Aviation University (archive), 2012)
The main features, characteristics and advantages of the open access database “Open Journal Systems” are considered. Demonstrated role of an electronic journal in promotion of the research activity and revealed the advantages of open access, through which expands readership and increases the number of citations of scientific papers.